EURASIA SPREADING BASIN TO LAPTEV SHELF TRANSITION: STRUCTURAL PATTERN AND HEAT FLOW - Drachev S.S.; Kaul N.; Beliaev V.N. (My University, 2003)
New geophysical data have become available from shipborne and satellite measurements allowing a re-evaluation of the largely unknown junction of the Arctic spreading centre and the northeastern Siberian continental margin where the transpolar mid-ocean Gakkel Ridge abuts against the continental slope of the Laptev Sea. Based on multichannel seismic reflection and gravity data, this sediment-covered spreading axis can be traced to the continental rise where it is cut-off by a transcurrent fault. Further continuation of the extensional axis into the continental slope can be attributed to two asymmetric grabens, which terminate against the prominent Khatanga-Lomonosov Fracture. Remnants of hydrothermal fauna and high heat-flow values of approximately 100 mW m-2 documented around these grabens in the up-slope area are typical for an oceanic spreading axis. Thus we consider these grabens to be morphotectonic termination of the global Atlantic-Arctic spreading system with plate motions shifting to the Khatanga-Lomonosov Fracture. The high heat flow and the distribution of earthquake epicentres allow us to assume that the present-day divergent plate tectonic boundary passes from the Gakkel Ridge to the eastern part of Laptev Sea with an offset of initial rifting along the Bel'kov-Svyatoi Nos Rift to the projected prolongation of the buried spreading axis by 140-150 km.
Keywords: Eurasia Basin; heat flow; Laptev Sea; ocean–continent transition; rifts; spreading